Landing mechanics between noninjured women and women with anterior cruciate ligament reconstruction during 2 jump tasks - Ortiz, A.; Olson, S.; Libby, C. L.; Trudelle-Jackson, E.; Kwon, Y.-H.; Etnyre, B.; Bartlett, W. (The American Journal of Sports Medicine, 2008)
Women with anterior cruciate ligament reconstruction have different neuromuscular strategies than noninjured women during functional tasks after ligament reconstruction and rehabilitation.